2022
DOI: 10.3390/ma15113799
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Mechanical Properties of Highly Filled PP/GTR Compounds

Abstract: Ground rubber from automobile tires is very difficult to recycle due to the cross-linking of the macromolecules and thus the lack of thermoplastic properties. The research consisted of assessing the processing possibility via the injection of highly filled PP/GTR compounds modified with 1.5 wt.% 2.5-dimethyl-2.5-di-(tert-butylperoxy)-hexane. GTR dosing ranged from 30 wt.% up to 90 wt.%. The evaluation of the processing properties of the obtained materials was carried out on the basis of the melt flow index tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…It can therefore be concluded that by selecting the appropriate cross-linking agent and manipulating the reactive processing parameters, it is possible to obtain products of higher quality without using an additional compatibilization technique. Similar findings were provided by Kosćiuszko et al 146 who compared GTR/polypropylene (PP) systems with and without 1.5 wt % 2.5-dimethyl-2.5-di(tert-butylperoxy)hexane. Except for the enhancement of mechanical properties, a significant improvement in the volume-flow rate (MVR) as a measure of processability was observed after the addition of the peroxide.…”
Section: ■ Fundamentals Of Gtr Recyclingsupporting
confidence: 82%
See 1 more Smart Citation
“…It can therefore be concluded that by selecting the appropriate cross-linking agent and manipulating the reactive processing parameters, it is possible to obtain products of higher quality without using an additional compatibilization technique. Similar findings were provided by Kosćiuszko et al 146 who compared GTR/polypropylene (PP) systems with and without 1.5 wt % 2.5-dimethyl-2.5-di(tert-butylperoxy)hexane. Except for the enhancement of mechanical properties, a significant improvement in the volume-flow rate (MVR) as a measure of processability was observed after the addition of the peroxide.…”
Section: ■ Fundamentals Of Gtr Recyclingsupporting
confidence: 82%
“…It can therefore be concluded that by selecting the appropriate cross-linking agent and manipulating the reactive processing parameters, it is possible to obtain products of higher quality without using an additional compatibilization technique. Similar findings were provided by Kościuszko et al . who compared GTR/polypropylene (PP) systems with and without 1.5 wt % 2.5-dimethyl-2.5-di­( tert -butylperoxy)­hexane.…”
Section: Green Rubber Recycling Technologiessupporting
confidence: 82%
“…Nowadays, the blending of GTR with various polymers, notably polypropylene (PP), polyethylene, polyvinyl chloride and polystyrene (Ramarad et al, 2015a(Ramarad et al, , 2015bJiang et al, 2018;Liang et al, 2020;Kosciuszko et al, 2022), has opened up avenues for shaping and re-melting these materials into a diverse array of extruded and moulded products. Consequently, GTR blends have found practical applications in numerous aspects of everyday life, including running tracks and playground surfaces, to name a few (Toncheva et al, 2021;Ferrao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of modified or unmodified GTR into polymer systems is a topic that has been addressed and studied for many years. GTR is usually added to thermoplastics such as polyethylene (PE) [ 16 , 17 , 18 ], polypropylene (PP) [ 19 , 20 , 21 ], polyvinyl chloride (PVC) [ 22 ], etc. It is also common to create blends based on natural or synthetic rubbers [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%